A Review of Trimen’s False Tiger Moth, Agoma trimenii (Lepidoptera: Agaristidae): Seasonal Biology, Potential Monitoring and Control Techniques - Morris, C.A.; Johnson, S.A.; De Waal, J.Y.; Malan, A.P. (South African Journal of Enology and Viticulture, 2020)
Trimen’s false tiger moth, Agoma trimenii (Lepidoptera: Agaristidae), has recently been found to occur in vineyards in the Northern Cape and Limpopo (Groblersdal area) provinces of South Africa. As little is known about the biology and behaviour of the moth, no official monitoring methods or economic thresholds relating to it, exist. Consequently, management and registered control options still require development. The first aim in the current review, was to gather and critically discuss all the available information on A. trimenii in the context of the information gained from field observations conducted in the Northern Cape, South Africa, during the 2016/2017 and 2017/2018 seasons. The paper also includes reporting on field observations made with regard to various aspects of the seasonal life cycle and ecology of A. trimenii, with a view to investigate, in future research, the potential biological control options available. Potential monitoring strategies of A. trimenii in the field were investigated. Various life stages of A. trimenii were identified, peak flight times were established, overlapping generations were determined, and the behavioural traits of all life stages were documented. Ultraviolet blue light traps proved to be the most promising potential monitoring strategy, with the prospect for an A. trimenii pheromone lure holding potential as an alternative monitoring strategy in future. With summarising all current information on A. trimenii, recommendations for growers to monitor and control A. trimenii are presented, towards the development of an integrated pest management system for the moth.